L'intégration du développement durable dans les universités françaises - Beigbeder, Sophie (Jihočeská univerzita, 2022)
This qualitative study focuses on sustainable development at the university, more specifically at the University of Le Mans and Rouen Normandie. The objective of this qualitative research is to understand what a responsible university is, to understand the institutional framework that governs universities and how SD can be integrated in HEIs. And finally, the main objective is to study what affects sustainable development in French universities. The question then arises as to how sustainable development is integrated in French universities. After a literature review, four interviews were conducted with members of the governance and project managers of the University of Le Mans and the University of Rouen Normandie in order to answer the question. The universities are in the midst of socio-ecological transitions and are carrying out actions in all the areas that make up a university: training and teaching, campus and research. Obstacles have been found to the integration of sustainable development. Governance through the centralisation of decisions and the lack (or not) of interest in the subject, the DDRS label through the roadmap and the continuous improvement that this provides. Another obstacle is the lack of involvement of staff and students, notably through ideology or simply lack of motivation. The regulation through public procurement that prevents the purchase of environmentally responsible goods and services is another big obstacle and finally the financial means and the allocation of these means to SD activities.
The integration of sustainable development in French universities
Keywords: développement durable; université durable; frein au développement durable; plan DDRS; sustainable development; sustainable university; sustainable development barrier; DDRS plan